THE INFLUENCE OF EMPLOYEE INTERACTION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - Lasagena, Mustamin; Idris; Kadang, Juliana (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This study is to determine and analyse the mainstreaming of Employee Interaction, Work Environment, and Job Satisfaction as mediating variables on employee performance at the Office of Highways and Spatial Planning of Central Sulawesi Province. The type of research used is quantitative research. The population in this study amounted to 188 with the number of respondents 65 employees with purposive sampling technique using the slovin formula. The analytical tool used in this research is Partial Least Square (PLS) 3.0. Data collection using questionnaires via google forms. The results showed that (1) Employee interaction has a positive and significant effect on employee performance. (2) The work environment has a positive and significant effect on employee performance. (3) Employee interaction has a positive and significant effect on employee job satisfaction. (4) Work environment has a positive and significant effect on employee job satisfaction. (5) Job satisfaction has a positive and significant effect on employee performance. (6) Employee interaction indirectly has a positive and significant effect on employee performance through job satisfaction. (7) The work environment indirectly has a positive and significant effect on employee performance through job satisfaction in employees of the Office of Highways and Spatial Planning of Central Sulawesi Province.